Graphical interface development for the position control of a 3RRR planar parallel manipulator - Burbano Castillo, Luis Carlos; Trullo Daza, Roger Peregrino; Daraviña Peña, Giancarlo; Quintero Riaza, Héctor Fabio (Scientia et Technica, 2018)
This paper presents the development of a graphicalinterface implemented in a 3-RRR planar parallel manipulator.The graphical interface allows the control, in open loop, of theposition of the manipulator, allowing to locate in the plane the endactuator and define its pose. The graphical interface allows thevisualization of variables such as angular position, torque, voltageof the servomotors that drive the input links. The theoretical andreal comparison of the angular displacement and the torque in themotors during the chosen path is shown, obtaining very closeresults between both.